Dismantling the Golden Age: Broadcast scheduling strategies on 1950s US network radio. - Arceneaux, Noah (Radio Journal: International Studies in Broadcast & Audio Media, 2023)
From the late 1940s to early 1960s, the US radio industry underwent a dramatic transformation. Instead of scripted programming and live musical performances, which characterized the era known as the Golden Age of Radio, stations began to focus on local advertising markets and relied upon recorded music for content. This study explores the programming and scheduling strategies of the major commercial networks in the United States as they dealt with this transformation. Using the theoretical framework of remediation, the analysis provides some context for a contemporary change in electronic media, the transition from linear programming to streaming and on-demand forms of delivery.